Sufistic Value in the Book of Ta’lim al Muta'alim Written by al Zarnuji (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2018)
This research examines in depth al-Zarnuji's thoughts about education, especially those relating among teacher and student with a sufistic approach. The object of the study is the ta'lim al muta'alim book written by al Zarnuji. Besides that, the writings of the figures who criticized the book were also examined. The purpose of this study, to know comprehensively al Zarnuji's thinking about the relationship of teacher with student in the teaching and learning process, especially those relating to their respective rights and obligations combined harmoniously with the concepts of teachings Sufism. This research is a literature study or analysis of documents, with emphasis on the analysis or interpretation of written material based on the context. The results of this study indicate that al-Zarnuji has provided a solution on how to create education that is not only worldly oriented, but also oriented towards the end. For example, in one discussion, it is revealed that: